2012
DOI: 10.1103/physrevb.86.155407
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarization andg-factor enhancement in graphene nanoribbons in a magnetic field

Abstract: We provide a systematic quantitative description of spin polarization in armchair and zigzag graphene nanoribbons (GNRs) in a perpendicular magnetic field. We first address spinless electrons within the Hartree approximation, studying the evolution of the magnetoband structure and formation of the compressible strips. We discuss the potential profile and the density distribution near the edges and the difference and similarities between armchair and zigzag edges. Accounting for the Zeeman interaction and descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…This is similar to the spin polarization of compressible strips in quantum wires and graphene nanoribbons in a high magnetic field. 29,33 For the case of the (2,1) GB, the corresponding state is fully occupied even for small applied V g , and therefore the spin-up and spin-down electron densities are the same. As a result, the potential felt by different spin species is the same and the spin polarization for the (2,1) state is completely suppressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the spin polarization of compressible strips in quantum wires and graphene nanoribbons in a high magnetic field. 29,33 For the case of the (2,1) GB, the corresponding state is fully occupied even for small applied V g , and therefore the spin-up and spin-down electron densities are the same. As a result, the potential felt by different spin species is the same and the spin polarization for the (2,1) state is completely suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…For the case of electrons with spin (σ = ↑,↓) we introduce spin-dependent electron densities n σ r and use the same formalism as described above with a Hubbard Hamiltonian of the form H = H ↑ + H ↓ , 29,31 …”
Section: Basicsmentioning
confidence: 99%
“…Here, we probe the total effective capacitance profile ( ) tot x α across ballistic graphene nanoconstrictions ( Fig.1b) with different degrees of edge disorder in a perpendicular magnetic field via magnetoconductance measurements. It is noteworthy that the local capacitance is accessible with these measurements in graphene devices [5,6,21], similar to conventional semiconductor structures defined in 2D electron gasses [5,22]. Indeed, magnetoconductance measurements are particularly relevant for the characterization of narrow (≤ 150 nm) confined channels [22], where alternative magnetocapacitance techniques are limited due to several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that electron-electron interactions modify electron conduction in GNRs substantially. 17,18 Specifically, when the electron Fermi level is not at the charge neutrality point, electrons are predicted to accumulate along the edges of the ribbon and therefore any edge imperfection may be expected to play an important role in transport. However, the interplay between this charge redistribution effect and edge reconstruction in the context of transport is yet to be examined either theoretically or experimentally.…”
Section: Introductionmentioning
confidence: 99%